Investigating the ohmic behavior of mediator-less microbial fuel cells using sewerage water as the bio-anode. Issue 1 (31st December 2022) - Mbarire, Thiong'o; Aloys, Osano; Chaka, Bakari
Abstract: There is a great challenge in ratification of electrochemical principles to energy-storage devices utilizing natural systems such as microbial fuel cells (MFCs). The purpose of this study is to investigate how increasing impedance affects key cell dynamics of MFCs at ambient conditions using untreated sewage as the bio-anode. A H-type mediator-less MFC of capacity 4, 556.25 cm 3 using porous graphite electrodes and raw sewage as the bio-anode was studied over one 10-day retention period. The results indicated an exponential increase in OCV up to the sixth day followed by its gradual reduction. ohmic behavior was observed in the current and power densities with the highest power density being 0.173 mW/cm 3 for the 1, 000 Ω resistor. The charge/discharge times ranged between 11.15 and 11.40 days with daily discharge rates of 8.77–8.96%. Ohmic behavior was also observed as the energy balance, capacity and density of the MFCs decreased with applied impedance. The highest values were obtained in the 1, 000 Ω MFC (energy balance, 336.1 J/s; energy capacity, 4.227 Wh/cm 3 and energy density, 17.237 Wh/kg, respectively). The MFCs ohmic behavior when using raw sewage proved to be quite novel and an inspiring finding to enhance applicability of MFCs using raw industrial effluents.